Pseudogap phase of cuprate superconductors confined by Fermi surface topology - N. Doiron-Leyraud (Nature Portfolio, 2017)
High-temperature superconductors exhibit pseudogap behaviour that remains of unknown origin, despite many years of intensive study. Here the authors study the onset of the pseudogap under pressure, providing evidence that it requires a hole-like Fermi surface and constraining future theoretical developments.